Enhancing Arabic Language Learning through Multiple Intelligences: A Qualitative Exploration in Islamic Secondary Education - Elok Rufaiqoh; Miftahul Huda; Ainur Firdansyah (https://unikhams.ac.id/, 2025)
Background of study : Arabic language learning often remains dominated by lecture-based methods, limiting student interaction and creativity. Applying Multiple Intelligences theory brings fresh possibilities to create more engaging and responsive classrooms. Aims and scope of paper: This study aims to examine how Arabic language instruction can be adapted using the Multiple Intelligences framework. It focuses on how instructional plans, classroom practices, and evaluation systems are designed to accommodate the varied cognitive strengths of students in Islamic secondary education. Methods: A qualitative descriptive approach was used, involving direct classroom observations, semi-structured interviews with teachers and students, and an indepth review of teaching documents such as lesson plans and syllabi. Data were analyzed using the Miles and Huberman framework, which includes data condensation, presentation, and interpretation. Result: Findings show that integrating MI principles into Arabic instruction allows teachers to address learners’ dominant intelligences—particularly verballinguistic, spatial, interpersonal, and intrapersonal. Lessons become more participatory, and assessment methods are expanded beyond written tests to include portfolios, reflective journals, and performance-based tasks. Conclusion: By aligning Arabic language teaching with the principles of Multiple Intelligences, educators can foster a richer, more inclusive learning atmosphere. This approach encourages learners to engage with the material in ways that resonate with their natural strengths, making the process of language acquisition more meaningful and personal.